Análise quimico-farmacêutica de Darunavir etanolato em comprimidos e de seu complexo de inclusão - Kogawa, Ana Carolina [UNESP] (2015)
The work aimed the formation of complex darunavir:β-cyclodextrin and the study of the consequences of complexation, as well as development and validation of analytical methods for qualitative and quantitative determination of darunavir in tablet (free) and complexed to β-cyclodextrin. darunavir free. The form of darunavir ethanolate was monitored throughout research time to ensure use of the same polymorph and no analytical differences. Qualitative analysis was performed by thin layer chromatography (TLC), ultraviolet spectrophotometry (UV), infrared spectroscopy (IR), liquid chromatography (LC) and capillary electrophoresis (CE) allowing the identification of darunavir ethanolate in tablets. More dynamic and environmentally friendly methods were validated for the quantification of darunavir ethanolate in pharmaceutical form using the IV and CE. The results of the validations were comparatively analyzed and techniques were equivalent and are therefore interchangeable. darunavir:β-ciclodextrina. Darunavir was complexed with β- cyclodextrin and confirmed by thermal techniques and studied by spectroscopic methods. Its properties were compared to the free drug as to solubility of inclusion complex and it is 28 times more soluble than darunavir when using buffer solution of 0.05 M acetate pH 4.5. This advance of pharmaceutical technology covers the resolution Best medicines for children discussed in the World Health Assembly, which launched the global campaign Make medicines child size. A method for quantification of darunavir in the complex was validated by LC coupled with mass spectrometry (LC-MS), with him were identified six degradation products, two from acid degradation, one from basic degradation and three from oxidative degradation. A developed TLC technique was adequate for visualizing all degradation products of complex darunavir:β-cyclodextrin observed in the CL method, being achieved faster and cheaper. Complex ...